Seasonality of ship emission related atmospheric pollution over coastal and open waters of the North Sea. (October 2020) - Bencs, László; Horemans, Benjamin; Buczyńska, Anna Jolanta; Deutsch, Felix; Degraeuwe, Bart; Van Poppel, Martine; Van Grieken, René
Abstract: The seasonal changes of a large set of atmospheric pollutants (i.e., gases, water-soluble aerosols, metallic/elemental components and black carbon (BC) content) have been studied over the southern bight of the North Sea (the Belgian Continental Shelf) and the English Channel during several marine sampling campaigns, carried out in 2010–2011. A coastal research station at De Haan, Belgium was concurrently used as a background air monitoring site. Size-segregated aerosols (PM1, PM2.5-1, PM10-2.5 ) were analyzed for particulate mass, elemental content and water-soluble (ionic) compounds, while the equivalent BC content in PM10 was monitored with an Aethalometer. The results clearly demonstrated that the aerosols originating from ship exhaust emissions contributed mostly to fine fraction (PM1 ), and to a lesser extent to medium-sized fraction (PM2.5-1 ), whereas components of sea spray and of mineral/soil origin were dominating in the medium-size and coarse aerosol fractions. Looking at seasonal differences, more ship emission related components occurred in the fine and medium-sized PM during winter. Mineral aerosol components were more apparent in coarse PM and especially during the cold season, increased levels were noted. Similarly, higher concentrations of marine fine PM were found during winter, likely due to more extensive ship emissions and/or calm weather conditions. Gaseous pollutants (e.g., HNO2, HNO3, HCl, SO2, NH3 ) originating from exhaust fumes of ocean-going ships mostly reached the maximum levels in the cold season as well, thus supporting the more intense formation of secondary aerosols. The seasonal trends of total (inorganic) ionic species sampled on the open sea and at the coastal station were usually similar to those of the corresponding PM masses, peaking in the cold season. Sea salt bound fine sulfate and nitrate peaked in spring or the cold season for marine areas, whereas for the coastal site they clearly reached the maximum in the cold season. Ammonium-bound nitrates and sulfates in each PM fraction reached their peak air levels in the cold season over marine sites. Similar seasonal trends could be observed for the coastal station. The general tendency of aerosol distribution over the study areas was independent of the sampling site: the higher the aerosol mass on the open sea with ship traffic, the higher the suspended particulate mass sampled at the coast. Graphical abstract: Image 1 Highlights: Marine and coastal pollutants of the North Sea were monitored and compared. Size-segregated aerosols, precursor gases, and BC were seasonally mapped. Ship exhaust contributed mainly to PM1, and with a less extent to PM2.5-1 . Pollutants peaked mostly over frequently navigated waters and in cold season. Coastal pollution levels followed those observed from ships over marine areas.